Design of Optimized and Innovative Remotely Operated Machine for Water Surface Garbage Assortment - Khekare, Ganesh S; Dhanre, Urvashi T; Dhanre, Gaurav T; Yede, Sarika S (International Journal of Computer Sciences and Engineering, 2019)
India is one of the largest countries in the world and holly also. In India many festivals are celebrated with brotherhood. So in the festivals like ganpati utsav, durga puja the garbage is discharge to the lakes or rivers in large amount. As the garbage is present in the river and lake, the water of river and lake gets contaminated. This polluted water affects the human lives if that contaminated water is used for drinking, the resident suffer from epidermal, gastrointestinal, neurological disorders and cardiac ailments. It also affects the species resides in the water. There is no small and fuel efficient device for collecting the garbage from river and lakes. The conventional machineries available in the market have very high cost as well as are not efficient. The conventional machineries are pedal operated and human efforts are required for the operation of machine. Some machineries use petrol or diesel for the operation. It is possible to clean the surface of water reservoirs by using remote operated river surface cleaning machine. By taking this into consideration our main motive is to clean water. For that purpose the remote operated river surface cleaning machine is useful. This water garbage collector machine is made up of DC motors, RF transmitter and receiver, propeller, PVC pipes and chain drive with the conveyor attached to it for collecting garbage from the lake.